2007
DOI: 10.3164/jcbn.40.141
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive and Antioxidant Action of Amlodipine and Vitamin C in Patients of Essential Hypertension

Abstract: Summary The etiology of essential hypertension includes increased oxidative stress. The role of antihypertensive drug amlodipine as an antioxidant and the benefit of addition of vitamin C, an antioxidant to antihypertensive therapy were studied. Forty male patients of essential hypertension were randomly divided into two groups and treated with 5 mg amlodipine. In addition one group also received 1000 mg vitamin C (as two 500 mg tablets) once daily for three months. Although blood pressure decreased in both gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 50 publications
1
32
1
1
Order By: Relevance
“…Vitamin C also seems to improve the efficacy of effective antihypertensive drugs such as amlodipine [46]. In elderly patients with refractory hypertension already on maximum pharmacologic therapy, 600 mg of vitamin C daily lowered the BP by 20 ± 8/16 ± 5 mmHg [47].…”
Section: Vitaminsmentioning
confidence: 99%
“…Vitamin C also seems to improve the efficacy of effective antihypertensive drugs such as amlodipine [46]. In elderly patients with refractory hypertension already on maximum pharmacologic therapy, 600 mg of vitamin C daily lowered the BP by 20 ± 8/16 ± 5 mmHg [47].…”
Section: Vitaminsmentioning
confidence: 99%
“…We could imply that antioxidant therapy itself could be effective enough in protection of brain tissue from the impairment in hypertension. In the literature there are studies using antioxidants for the treatment of hypertension in patients as well as in SHR (Mahajan et al 2007;Eshginia and Gapparov 2006;Czernichow et al 2005). Vitamin E supplementation significantly attenuated the increase in BP, intracellular calcium concentration, renal tissue aldehyde conjugates, and adverse renal vascular changes (Vasdev et al 2002) in SHR.…”
Section: Discussionmentioning
confidence: 96%
“…A serum level of 100 μmol/L is recommended [1,70,71] . The SBP and 24 ABM show the most significant reductions with chronic oral administration of Vitamin C [200][201][202][203][204][205] . Block et al [206] in an elegant depletion-repletion study of vitamin C demonstrated an inverse correlation of plasma ascorbate levels, SBP and DBP.…”
Section: Fibermentioning
confidence: 99%
“…Vitamin C prevents ED induced by an oral glucose load. Vitamin C enhances the efficacy of amlodipine, decreases the binding affinity of the AT 1 receptor for angiotensin Ⅱ by disrupting the ATR1 disulfide bridges and enhances the anti-hypertensive effects of medications in the elderly Houston M. Hypertension, nutrition, nutritional supplements, cardiovascular disease with refractory hypertension [1,70,71,[200][201][202][203][204][205] . In elderly patients with refractory hypertension already on maximum pharmacologic therapy, 600 mg of vitamin C daily lowered the BP by 20/16 mmHg [205] .…”
Section: Fibermentioning
confidence: 99%
See 1 more Smart Citation